2022
DOI: 10.3390/membranes12040406
|View full text |Cite
|
Sign up to set email alerts
|

MXene (Ti3C2Tx)/Cellulose Acetate Mixed-Matrix Membrane Enhances Fouling Resistance and Rejection in the Crossflow Filtration Process

Abstract: Obstacles in the membrane-based separation field are mainly related to membrane fouling. This study involved the synthesis and utilization of covalently crosslinked MXene/cellulose acetate mixed matrix membranes with MXene at different concentrations (CCAM-0% to CCAM-12%) for water purification applications. The membranes’ water flux, dye, and protein rejection performances were compared using dead-end (DE) and crossflow (CF) filtration. The fabricated membranes, especially CCAM-10%, exhibited high hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Previous studies have established a correlation between the antifouling ability of MMMs and key membrane properties such as hydrophilicity, porosity, and surface roughness. , The literature consistently demonstrates that hydrophilicity plays a crucial role in influencing membrane fouling behavior. Increased hydrophilicity promotes the formation of a hydration layer on the membrane surface, which impedes the adsorption of organic foulants onto the membrane’s surface Figure displays the time-resolved contact angle of the membrane samples, revealing that PAN-PDA-Ak/NaOH had the highest wettability, with a rapid decrease in contact angle and complete water droplet absorption within 1 s of contact.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have established a correlation between the antifouling ability of MMMs and key membrane properties such as hydrophilicity, porosity, and surface roughness. , The literature consistently demonstrates that hydrophilicity plays a crucial role in influencing membrane fouling behavior. Increased hydrophilicity promotes the formation of a hydration layer on the membrane surface, which impedes the adsorption of organic foulants onto the membrane’s surface Figure displays the time-resolved contact angle of the membrane samples, revealing that PAN-PDA-Ak/NaOH had the highest wettability, with a rapid decrease in contact angle and complete water droplet absorption within 1 s of contact.…”
Section: Resultsmentioning
confidence: 94%
“…64 Previous studies have established a correlation between the antifouling ability of MMMs and key membrane properties such as hydrophilicity, porosity, and surface roughness. 65,66 The literature consistently demonstrates that hydrophilicity plays a crucial role in influencing membrane fouling behavior. Increased hydrophilicity promotes the formation of a hydration layer on the membrane surface, which impedes the adsorption of organic foulants onto the membrane's surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a hydrophilic nanofiltration membrane is commonly considered to be a filter type which facilitates the permeation of water through the film while a hydration layer formed on the surface due to the adhesion of water molecules suppresses the accumulation of the hydrophobic foulants on the surface (which can be considered as an adhesion-type antifouling effect in this case). [45k] In terms of the structures and materials, as the most studied species, Ti 3 C 2 T x MXenes are applied in different areas in the form of powders, [116] coatings on fibers, [117] free-standing films, [97] and 3D architectures (such as foams and aerogels) [70,118] with desirable wettability. Besides, the wetting properties of MXenes, in many cases, have been adjusted by chemical modification and/ or hybridization strategies where they can act as the additive, [94] matrix, [85] and supporting substrate [119] in a particular system.…”
Section: Wettability-related Applicationsmentioning
confidence: 99%
“…It has been shown that the modification with the introduction of a hydrophobic crosslinking agent into the anion exchange membrane makes it possible to simultaneously achieve high electrical conductivity and a low swelling ratio [ 95 ]. On the other hand, for other processes, an increase in the resistance to fouling after the introduction of a hydrophilic crosslink was shown in [ 96 ], where it was also found that the membrane with the highest fraction of the introduced crosslinking agent possesses the highest resistance to fouling. Hence, it might be concluded that increased crosslinking improves the fouling resistance regardless of composition of crosslinking agent.…”
Section: Approaches To Prevention Of Degradationmentioning
confidence: 99%